From entrepreneurial passion to entrepreneurial intentions: The role of entrepreneurial passion, innovativeness, and curiosity in driving entrepreneurial intentions. (15th April 2020) - Syed, Imran; Butler, Jonathan Craig; Smith, Ronda M.; Cao, Xian
Highlights: Paper explores entrepreneurial passion to entrepreneurial intentions relationship. Innovativeness partially mediates the passion to intentions relationship. Curiosity positively moderates the passion to intentions mediated relationship. Abstract: Previous studies have shown that entrepreneurial passion has a positive relationship with entrepreneurial intentions, however we do not know much about the underlying mechanisms that might mediate or moderate this relationship. This study extends the existing literature by examining the mediating role of innovativeness and the moderating role of curiosity in the entrepreneurial passion to entrepreneurial intentions relationship. Results, based on analysis of data collected from 295 respondents, showed that innovativeness partially mediated the entrepreneurial passion to entrepreneurial intentions relationship. Further, the mediating effect was stronger for individuals who scored high on curiosity than for individuals who scored low on curiosity. The present study contributes to a better understanding of the how, and the when of how, of the entrepreneurial passion to entrepreneurial intentions relationship.